2020
DOI: 10.1108/k-06-2020-0365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patent documents with utility mining: a case study of wind energy technology

Abstract: Purpose This study aims to propose a novel approach based on utility mining to find the associations among wind energy technologies. Design/methodology/approach The proposed approach uses patent documents and utility mining. Associations among wind energy technologies have been evaluated to show how the proposed approach works in practice. Findings Determining the relationships between wind energy technologies provide essential information to investors and decision-makers. Therefore, a real-life case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In terms on research limitations, three main restrictions including: (1) Lack of integrated software to perform calculations of fuzzy DEMATEL technique increases the time of calculations and the probability of errors in calculations. (2) The impossibility of checking the accuracy of the answers is another limitation in studies which data is formed according to the respondents' opinions. (3) Using the concept of OI in MSMEs in developing countries such as Iran is considered as a new approach and this makes it not only difficult to find competent people to answer research questions, but also different dimensions are still needed for study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms on research limitations, three main restrictions including: (1) Lack of integrated software to perform calculations of fuzzy DEMATEL technique increases the time of calculations and the probability of errors in calculations. (2) The impossibility of checking the accuracy of the answers is another limitation in studies which data is formed according to the respondents' opinions. (3) Using the concept of OI in MSMEs in developing countries such as Iran is considered as a new approach and this makes it not only difficult to find competent people to answer research questions, but also different dimensions are still needed for study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in OI paradigm, which was first introduced by Henry Chesbrough in 2003 [5,47], knowledge is transferred easily from inside and outside of the organizations [25,28]. Thus, firms cannot rely on their internal research and they can benefit from purchasing innovations or licenses from other companies if necessary [2]. In fact, OI is a process, in which external ideas are welcomed as well as internal ones [29] and the borders between organizations and environment are penetrable, which facilitates knowledge transfer [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patent data can be analyzed to identify multiple dimensions of an innovation landscape. Using patent analysis, previous studies have identified trends and trajectories of evolving and established technologies [3][4], technology convergence and divergence, and firm innovation capabilities. Patent citation analysis is employed to assess the knowledge flow [5][6], as well as knowledge providers and absorbers [7] across the technology trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…• Development of new analysis methodologies using patents documents on wind and other renewable energy as application examples (Daim et al, 2012;De Rassenfosse et al, 2013;Altuntas & Gök, 2020).…”
Section: Introductionmentioning
confidence: 99%